Fermentation of the milk base with the natural formation of breast milk oligosaccharides — new opportunities in the adaptation of infant formula - O. N. Komarova; A. I. Danilova (Лечащий Врач)
Background. Breast milk is the best nutrition for a baby. If breastfeeding is not possible, the choice of infant formula is of paramount importance. It is important that the composition of the formula reflects the composition and effects of breast milk. A new approach to adapting infant formula is a special technology for fermenting the milk base. It has been demonstrated that as a result of fermentation, partial breakdown of macronutrients occurs, which increases the biological value and facilitates the digestion of the dairy product. Also, during the fermentation of the milk base by bacterial strains, their metabolic products are formed – various metabolically active compounds, postbiotics, which bring health benefits to the host organism.Objective. To evaluate the scientific evidence presented in the national and international literature on the biological value of fermented foods, the effect of the fermentation process on macronutrients, and the benefits of using a fermented milk base in infant formula.Results. Analysis of the literature demonstrates high scientific interest in the topic under review. The benefits of fermented foods are due, among other things, to the formation of active metabolites of lactic acid bacteria, postbiotics. The class of postbiotics includes a wide range of compounds, for example: peptides, amino acids, fatty acids, breast milk oligosaccharides, etc. The quality and quantity of postbiotics is determined by the type of bacteria used to ferment the product, as well as the characteristics of the ripening technology. The use of a partially fermented milk base to create infant formula is an innovative approach in adapting breast milk substitutes because it allows us to get closer to the composition and effect of breast milk. One of the postbiotics formed as a result of Lactofidus™ fermentation is the oligosaccharide 3’-galactosyllactose (3’-GL), identical in structure and properties to 3’-GL of breast milk. In vivo and in vitro studies have shown the safety and good tolerability of infant formulas containing 3'-GL, as well as their positive effects on the child’s body at the local and systemic levels, in particular, in combination with prebiotics scGOS/lcFOS (9:1).